Some Properties and Inequalities for the h,s-Nonconvex Functions - Chengli Wang; Muhammad Shoaib Saleem; Hamood Ur Rehman; Muhammad Imran (Journal of Mathematics)
The purpose of this paper is to introduce the notion of strongly h,s-nonconvex functions and to present some basic properties of this class of functions. We present Schur inequality, Jensen inequality, Hermite–Hadamard inequality, and weighted version of the Hermite–Hadamard inequality.